Emerging food and nutrition security challenges in Central Asia: Implications for BRICS and emerging economies - Babu, Suresh Chandra; Akramov, Kamiljon T. (Oxford University Press, 2021)
In the last two decades, Central Asia has gone through several transitions in institutions and governance, each with consequences for the agricultural sectors in the region. Since their independence, the five countries Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan, and Uzbekistan, have made considerable progress towards increasing domestic food production. However, food security in the region is still threatened by major geopolitical and socio-economic challenges. Lack of support from institutions to advance farming has resulted in the low level of food security in the region. Lack of research and extension of support to farmers and low capacity for designing evidence-based policies are major challenges to the region’s food security. This chapter identifies critical issues and challenges faced by Central Asian countries for attaining short-term and long-term food and nutrition security, and the implications for BRICS and other emerging economies.